Efektivitas Zakat Pada Aplikasi Digital Lembaga Amil Zakat Dalam Pembangunan Ekonomi - Cita Restuningsih; Stefany Caroline; Agus Munandar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine how effective digital applications and websites of amil zakat institutions are in economic development. A qualitative analysis approach was used in this research method. The objects of this research are LAZ YAKESMA, LAZ Rumah Zakat and LAZ Dompet Dhuafa. The results showed that the three amil zakat institutions have received and distributed zakat funds to beneficiaries, but LAZ Dompet Dhuafa experienced a deficit in distributing zakat funds. LAZ YAKESMA and LAZ Rumah Zakat overall receive and distribute the allocation of zakat funds effectively with an absorption rate of 67% and 83% respectively. Keywords: Zakat Effectiveness, Application of LAZ, Economic Development